2009
DOI: 10.1093/applin/amp012
|View full text |Cite
|
Sign up to set email alerts
|

Seizure, Fit or Attack? The Use of Diagnostic Labels by Patients with Epileptic or Non-epileptic Seizures

Abstract: We present an analysis of the use of diagnostic labels such as seizure, attack, fit and blackout by patients who experience seizures. While previous research on patients' preferences for diagnostic terminology has relied on questionnaires, we assess patients' own preferences and their responses to a doctor's use of different labels through the qualitative and quantitative analysis of doctor-patient interactions in a realistic clinical setting. We also examine whether two subgroups of patients -those with epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…This observation is very much in keeping with those made in previous studies of dyadic interactions between seizure patients and doctors [1][2][27][28][29][30][31][32][33][34]. We found that these differences in the interactional behaviour of patients are closely associated with differences in the interactional contributions made by their companions.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is very much in keeping with those made in previous studies of dyadic interactions between seizure patients and doctors [1][2][27][28][29][30][31][32][33][34]. We found that these differences in the interactional behaviour of patients are closely associated with differences in the interactional contributions made by their companions.…”
Section: Discussionsupporting
confidence: 91%
“…Narratives of patients with epilepsy typically normalise seizure experiences whereas patients with PNES often catastrophise [55]. Patients with epilepsy are happy to call their main symptom a seizure whereas those with PNES often avoid labels and prefer pronouns [56]. These observations concur with other data suggesting that many patients with PNES have an avoidant coping style [57,58], and that the attacks themselves are often an anxiety-based phenomenon, albeit not one that is always recognised as such by patients.…”
Section: Interactional Representationsupporting
confidence: 81%
“…This observation is in keeping with another study focusing on the use of the medical labels which found that patients with NEAD were more likely than those with epilepsy to resist terms such as "seizure" or "attack" which imply that ictal symptoms are the consequence of an external agent acting on the patients' body [54]. It also fits with the findings of a study in which 48 patients with video-EEG proven epilepsy or NEAD were contacted after a major earthquake: 23% of patients with epilepsy but none with NEAD volunteered that they thought that they were going into a seizure when they first became aware of the earthquake [78].…”
Section: Subjective Seizure Experiencesupporting
confidence: 86%